Iš kur atsirado senųjų raštų hukis „ūkis“, horas „oras“ ir kt.? - Zinkevičius, Zigmas (Baltistica, 1984)
A note on the use of Old Lith. hukis ʽūkis’, horas ʽoras’ and other forms In the Lithuanian writings of the 16th–17th century words which began with a vowel were sometimes preceded by h. This phenomenon is accounted for as hypernormalism, i. e. an imitation of the borrowings which in the original had h, but in Folk Lithuanian had lost the sound. As in the writings of the same author we can find both variants (e. g. hadyna ‖ adyna ʽvalanda’, hūtaryti ‖ ūtaryti ʽkalbėti’), one could easily mistake the forms and add h to Lithuanian words beginning with a vowel (e. g. haiškus, herelis, horas, hožys, hūkis, hūžimas instead of the usual forms aiškus, erelis, oras, ožys, ūkis, ūžimas).